2013
DOI: 10.1155/2013/735290
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Reduction of Asymmetry in Human Central Auditory Function: A 1H-Magnetic Resonance Spectroscopy Study

Abstract: The aim of this study was to investigate the effects of age on hemispheric asymmetry in the auditory cortex after pure tone stimulation. Ten young and 8 older healthy volunteers took part in this study. Two-dimensional multivoxel 1H-magnetic resonance spectroscopy scans were performed before and after stimulation. The ratios of N-acetylaspartate (NAA), glutamate/glutamine (Glx), and γ-amino butyric acid (GABA) to creatine (Cr) were determined and compared between the two groups. The distribution of metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 25 publications
(22 reference statements)
1
12
1
Order By: Relevance
“…Profant et al (2015) did not observe a significant effect of age on GABA levels in auditory cortex. In contrast, Chen et al (2013) did report a significant decline in GABA levels: in the right (but not the left) hemisphere before pure tone stimulation, and in both hemispheres after stimulation. Likewise, Gao et al (2015) reported that older adults suffering from age-related hearing loss exhibited lower GABA levels in auditory cortex compared to other older adults.…”
Section: Age-related Decline In Gaba Levelscontrasting
confidence: 62%
See 1 more Smart Citation
“…Profant et al (2015) did not observe a significant effect of age on GABA levels in auditory cortex. In contrast, Chen et al (2013) did report a significant decline in GABA levels: in the right (but not the left) hemisphere before pure tone stimulation, and in both hemispheres after stimulation. Likewise, Gao et al (2015) reported that older adults suffering from age-related hearing loss exhibited lower GABA levels in auditory cortex compared to other older adults.…”
Section: Age-related Decline In Gaba Levelscontrasting
confidence: 62%
“…Most previous neural dedifferentiation studies have been focused on the visual cortex, and so it remains unclear whether dedifferentiation also occurs in other sensory regions, such as the auditory cortex. Furthermore, the results of the small number of human studies investigating age-related changes in GABA levels in the auditory cortex are mixed (20,21). In the present study, we therefore asked whether older adults would have reduced distinctiveness and reduced GABA levels in the auditory cortex compared with young adults.…”
Section: Introductionmentioning
confidence: 93%
“…An alternative explanation for age-related differences in hemispheric asymmetry has been offered by Chen et al ( 2013 ). In this study, young (18–27 years) and older adults (55–75 years) with clinically normal hearing underwent magnetic resonance spectroscopy scans in order to investigate hemispheric contents of glutamate and GABA, two neurotransmitters that mediate excitatory and inhibitory processes.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the NAA percentage is used to evaluate neuronal damage or loss. Spectroscopic investigations have demonstrated that NAA concentrations in the temporal-auditory brain regions decrease with advancing age, reflecting neuronal dysfunction and/or loss in the aging brain (Angelie et al, 2001 ; Chen et al, 2013 ). This NAA observation is consistent with imaging studies demonstrating an age-related reduction in brain volume (e.g., Matsumae et al, 1996 ; Lim and Spielman, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, asymmetry between the two ear test results increases as the corpus callosum atrophies increase in the isthmus and splenium regions during the aging [8]. However findings from a large number of dichotic listening tests indicate that asymmetry of speech processing increases in elderly people, regardless of hearing loss [4,8,9]. Dichotic ability can be evaluated using several tests of central auditory system that involve listening to competing signals challenging the auditory system and cognitive function.…”
Section: Introductionmentioning
confidence: 99%